2018
DOI: 10.1186/s12885-017-3919-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving zebrafish embryo xenotransplantation conditions by increasing incubation temperature and establishing a proliferation index with ZFtool

Abstract: BackgroundZebrafish (Danio rerio) is a model organism that has emerged as a tool for cancer research, cancer being the second most common cause of death after cardiovascular disease for humans in the developed world. Zebrafish is a useful model for xenotransplantation of human cancer cells and toxicity studies of different chemotherapeutic compounds in vivo. Compared to the murine model, the zebrafish model is faster, can be screened using high-throughput methods and has a lower maintenance cost, making it pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 30 publications
1
53
0
Order By: Relevance
“…Raising the temperature might improve survival of human CD34 cells, as it will provide a more ‘human like’ environment, without affecting the embryos development. Indeed, raising zebrafish embryos at a higher temperature of 36 °C after xenotransplantation of human tumour cells showed no effect on embryo survival and improved survival of the human cells ( Cabezas-Sainz et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Raising the temperature might improve survival of human CD34 cells, as it will provide a more ‘human like’ environment, without affecting the embryos development. Indeed, raising zebrafish embryos at a higher temperature of 36 °C after xenotransplantation of human tumour cells showed no effect on embryo survival and improved survival of the human cells ( Cabezas-Sainz et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, zebrafish become a suitable model for oncology research using the approach of xenotransplantation of human cancer cells into the yolk sac of a zebrafish embryo. Nowadays, zebrafish embryos are widely used to study the toxicity assessment of various drugs and bioactive metabolites due to its experimental reliability and also low expansive model 42,43 . Our toxicity study revealed that four DKPs did not show any significant mortality rate and developmental changes of the zebrafish embryos after exposure with 96 hpf.…”
Section: Discussionmentioning
confidence: 99%
“…28.5°C according to published procedures 35 . All the procedures used in the experiments as well as fish care were performed in agreement with the Animal Care and Use Committee of the University of Santiago de Compostela and the standard protocols of Spain (Directive 2012-63-UE).…”
Section: Methodsmentioning
confidence: 99%
“…To functionally test the invasive capacity of Gal-CC and Gluc-CC, zebrafish and NOD-SCID mouse models of cellular invasion were employed. Zebrafish embryos were microinjected into circulation (Duct of Cuvier), as previously described 35 . While at 1 day post- injection (dpi) PANCA6L mCherry-H2B Gluc-CC migrated more efficiently to the tail compared to Gal-CC (Fig.…”
Section: Upregulated In Vivo Immune Evasion and Metastasis In Gal-ccmentioning
confidence: 99%